Local health department engagement with workplaces during the COVID-19 pandemic-Examining barriers of and facilitators to outbreak investigation and mitigation - Tessa Bonney; Michael P. Grant (Frontiers Media S.A., 2023)
ObjectivesTo document local health department (LHD) COVID-19 prevention or mitigation activities at workplaces in the United States and identify facilitators for and barriers to these efforts.MethodsWe conducted a web-based, cross-sectional national probability survey of United States LHDs (n = 181 unweighted; n = 2,284 weighted) from January to March 2022, collecting information about worker complaints, surveillance, investigations, relationships and interactions with employers/businesses, and LHD capacity.ResultsOverall, 94% LHD respondents reported investigating workplace-linked COVID-19 cases; however, 47% reported insufficient capacity to effectively receive, investigate and respond to COVID-19-related workplace safety complaints. Prior relationships with jurisdiction employers and LHD personnel with formal occupational health and safety (OHS) training were predictors of proactive outreach to prevent COVID-19 spread in workplaces (p < 0.01 and p < 0.001). LHD size predicted OHS personnel and sufficient financial resources to support workplace investigation and mitigation activities (p < 0.001).ConclusionsDifferences in LHD capacity to effectively respond to communicable disease spread in workplaces may exacerbate health disparities, especially between rural and urban settings. Improving LHD OHS capacity, especially in smaller jurisdictions, could facilitate effective prevention and mitigation of workplace communicable disease spread.